If x = 3 is a solution of the equation

Question:

If $x=3$ is a solution of the equation $3 x^{2}+(k-1) x+9=0$, then $k=?$

(a) 11
(b) −11
(c) 13
(d) −13

 

Solution:

(b) −11

It is given that $x=3$ is a solution of $3 x^{2}+(k-1) x+9=0$; therefore, we have:

$3(3)^{2}+(k-1) \times 3+9=0$

$\Rightarrow 27+3(k-1)+9=0$

$\Rightarrow 3(k-1)=-36$

$\Rightarrow(k-1)=-12$

$\Rightarrow k=-11$

 

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now